Co-digestion approach for enhancement of biogas production by mixture of untreated napier grass and industrial hydrolyzed food waste - Kriswantoro, Jayen Aris; Pan, Kuan-Yin; Chu, Chen-Yeon (Frontiers in Bioengineering and Biotechnology, 2024)
The co-digestion of untreated Napier grass (NG) and industrial hydrolyzed food waste (FW) was carried out in the batch reactor to investigate the effect of substrate ratios on biogas production performance. Two-stage anaerobic digestion was performed with an initial substrate concentration of 5 g VSadded/L and a Food to Microorganism Ratio (F/M) of 0.84. The 1:1 ratio of the NG and FW showed the optimum performances on biogas production yield with a value of 1,161.33 mL/g VSadded after 60 days of digestion. This was followed by the data on methane yield and concentration were 614.37 mL/g VSadded and 67.29%, respectively. The results were similar to the simulation results using a modified Gompertz model, which had a higher potential methane production and maximum production rate, as well as a shorter lag phase and a coefficient of determination of 0.9945. These findings indicated that the co-digestion of Napier grass and hydrolyzed food waste can enhance biogas production in two-stage anaerobic digestion.